Describing the linkage between administrative social assistance and health care databases in Ontario, Canada. (2022) - Oliveira, Claire de; Gatov, Evgenia; Rosella, Laura; Chen, Simon; Strauss, Rachel; Azimaee, Mahmoud; Paterno, Elizabeth; Guttmann, Astrid; Children, Ministry of; Community, Community; Chong, Social Services-ICES Working Group (Nelson; Ionescu, Peter; et al.
No abstract available